Exploiting parallelism by data dependency elimination : a case study of circuit simulation algorithms - Wu, Wei (2013)
Considering the increasing complexity of integrated circuit (IC) designs at Nano-Tera scale, multi-core CPUs and many-core GPUs have provided ideal hardware platforms for emerging parallel algorithm developments in electronic design automation (EDA). However, it has become extremely challenging to leverage parallel hardware platforms at extreme scale beyond 22nm and 60GHz where the EDA algorithms, such as circuit simulation, show strong data dependencies. This paper presents data dependency elimination in circuit simulation algorithms such as parasitic extraction, transient simulation and periodic-steady-state (PSS) simulation, which paves the way towards unleashing the underlying power of parallel hardware platforms.